Optimalisasi Pelaksanaan Pekerjaan Dengan Menggunakan Metode Crashing pada Proyek Peningkatan Struktur Jalan Laha-Negeri Lima. - Tuhuteru, Ilham; Sangadji, Fauzan A.; Oppier, Imran; Latuconsina, Syafruddin Ishak (Sekolah Tinggi Teknologi Dumai, 2024)
The problem that often occurs in construction projects is delay. The Laha Negri Lima Road Structural Improvement Development Project was chosen for the case study because it experienced a progress delay in its implementation of 12.16% at 17.31% progress. which causes the total project completion time to be longer, with a planned project completion time of 210 days. The aim of this research is to determine the minimum cost and optimum duration of acceleration using the crashing method. Also assisted by using Microsoft Project 2010 software to determine the project's critical path and create a simulation model in the form of a new schedule after acceleration analysis. The alternative project acceleration used is an additional 2 hours (overtime). The results of the analysis for the alternative of adding 2 working hours (overtime) obtained a time of 129 days with a cost efficiency of Rp. 214,719,386.87 The results of the analysis show that accelerating the project with the alternative of adding 2 hours of overtime work results in less total time and costs compared to the normal duration.